2019
DOI: 10.1590/0034-7167-2018-0273
|View full text |Cite
|
Sign up to set email alerts
|

Hospital care and urinary incontinence in the elderly

Abstract: Objective: to identify factors inherent in hospital care that favor urinary incontinence in the elderly. Method: an integrative review with Scopus, CINAHL and Pubmed searches. Includes original articles, no language restriction, published between 2008 and 2018. Rated level of recommendation and level of evidence were assessed using the Oxford Center for Evidence-Based Medicine classification. Exploited content through thematic analysis in light of the Donabedian model. Results: 13 articles constituted the sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
21

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(42 citation statements)
references
References 21 publications
0
21
0
21
Order By: Relevance
“…In this case, P: older adults; I: hospitalization; C: factors inherent to the care that predispose the event, and O: onset of UI. Thus, the following research question was formulated: What are the inherent factors to hospital care that predispose the onset of UI in older adults (4) ?…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…In this case, P: older adults; I: hospitalization; C: factors inherent to the care that predispose the event, and O: onset of UI. Thus, the following research question was formulated: What are the inherent factors to hospital care that predispose the onset of UI in older adults (4) ?…”
Section: Methodsmentioning
confidence: 99%
“…The UI problem is multifactorial and studies (3)(4) have revealed that the hospital structure and environment are extrinsic factors strongly related to its appearance or worsening. resources, information systems and technicaladministrative normative instruments up to political support and organizational conditions (5) .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations